RICE FIELDS MANAGEMENT AGREEMENT SYSTEM IN ACEH BESAR (Study of Engagement Patterns and Sharing of Harvest Results) - Irwansyah Muhammad Jamal; Zaiyad Zubaidi (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2023)
Rice field management, which is carried out by involving the people of Aceh Besar based on the norms of Islamic law and customary law, is applied from the beginning of the determination of the engagement to the capital of the harvest. Community practice describes the procedure for contracting and distributing crops in various forms. However, all farmers do it by mutual consent. This phenomenon is the focus of study in this paper. By basing on the method of discriptive analysis, the answers will be found, including: 1) the formation of contracts is carried out orally. The form of an oral contract is based on several things, namely the relationship between the parties; In general, the parties come from relatives or close family. Because of this relationship, they believe there will be no default made by the parties. In addition, there are two ways to start involvement in rice field management; First, half of the respondents agreed that capital is borne by rice field owners (this model is called muzara'ah), and half said capital is borne by farmers (this model is called mukhabarah). 2) the distribution of crops is carried out in the following way; 1) Mawah, which is divided equally between rice field owners and farmers. There are 3 people (20%); 2) Bulung 3, which is 2 parts for farmers, 1 part for rice field owners = 5 people (33.3%); 3) Bulung 4, which is 3 parts for farmers, 1 part for rice field owners = 4 people (26.6%); 4) Bulung 5, which is 3 parts for farmers, 2 parts for rice field owners =3 (20.1%). In addition to the three things already mentioned, the parties also agreed on the conditions of crop failure. Most engagements exempt farmers from giving rice to rice owners as a cost of using rice fields, while others require farmers to give rice to rice owners as rice field use fees.